Point-of-Care Gastric Ultrasound Confirms the Inaccuracy of Gastric Residual Volume Measurement by Aspiration in Critically Ill Children: GastriPed Study - Valla, Frederic V.; Cercueil, Eloise; Morice, Claire; Tume, Lyvonne N.; Bouvet, Lionel (Frontiers in Pediatrics, 2022)
Introduction: No consensus exists on how to define enteral nutrition tolerance in critically ill children and the relevance of gastric residual volume (GRV) is currently debated. The use of point of care ultrasounding (POCUS) is increasing among pediatric intensivists, and gastric POCUS may offer a new bedside tool to assess feeding tolerance and pre-procedural status of the stomach content. Material and methods: a prospective observational study was conducted in a tertiary pediatric intensive care unit. Children on mechanical ventilation and enteral nutrition were included. Gastric POCUS was performed to assess gastric contents (empty, full of liquids or solids) and gastric volume was calculated as per Spencer formula. Then, GRV was aspirated and measured. A second set of gastric POCUS measurements was performed, similarly to the first one performed prior to GRV measurement. The ability of GRV measurement to empty the stomach was compared to POCUS findings. Both GRV and POCUS gastric volumes were compared with any clinical signs of enteral feeding intolerance (vomiting). Results: Data from 64 children were analyzed. Gastric volumes were decreased between the POCUS measurements performed pre and post GRV aspiration (full stomach n=59 (92.2%) decreased to n=46 (71.9%), P=0.001; gastric volume: 3.18 (2.40-4.60) mL/kg decreased to 2.65 (1.57-3.57), P<0.001). However, the stomach was not empty after GRV aspiration in 46/64 (71.9%) of the children. There was no association between signs of enteral feeding intolerance and the GRV obtained, nor with gastric volume measured with POCUS. Discussion: GRV aspiration failed to empty the stomach and appeared unreliable as a measure of gastric emptiness. Gastric POCUS needs further evaluation to confirm its role.